STRATEGI PENGEMBANGAN USAHA PENGOLAHAN HERBAL TRADISIONAL DI GERANTING - KOTA BATAM - Kamaruzaman; Andaristi, Lusy (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2024)
Traditional herbal businesses have prospects for growth, but are still not able to because of limitations. The aim of this research is to analyze internal and exter-nal environmental factors as well as to formulate a strategy for developing a traditional herbal processing business in Geranting, Batam with a SWOT analysis. The results of the strategy formulation with SWOT analysis are obtained by optimally capturing opportunities by empowering the re-sources/strengths they have, such as increasing production, capital, technology, licensing and services. Covering weaknesses by building cooperation in terms of machinery, management, products, infrastructure and transportation. Overcom-ing obstacles with strengths such as increasing promotions, sales, purchasing contracts, information on herbal properties, prioritizing support needs. Strate-gies to survive in weak conditions and many obstacles, namely by joining technology, holding on to existing advantages, following other management, reducing infrastructure, setting agendas for the city.